Study on Influencing Factors of Policy Agricultural Insurance Performance in Guangdong Province - Xiao , Zou; Orunruk, Sorn Sutthikhun (Journal of Roi Kaensarn Academi, 2024)
The aim of this study was to explore the key factors influencing the performance of policy-based agricultural insurance in Guangdong Province and suggest policy optimization. We analyze the relationship between the government, insurance companies and farmers. The expert interviews revealed the impact of farmers’ insurance awareness, government subsidies, claims efficiency, product flexibility and local government implementation on performance. In the quantitative study, data were collected in eastern, central and western Guangdong by regional stratified sampling, and structural equation model (SEM) was used for analysis. Quantitative analysis verified the significant impact of government policy support, insurance supply capacity and farmers’ demand on insurance performance. Through a combination of qualitative and quantitative research, this study not only verifies the hypothesis, but also provides practical recommendations for policy makers and insurance institutions to optimize policies and services. These findings have important theoretical and practical significance to improve the performance of policy-based agricultural insurance in Guangdong province, enhance farmers’ insurance willingness, and promote the green development of agriculture.